Adsorption Behaviour of Reduced Graphene Oxide for Removal of Heavy Metal Ions - Wang, Bo; Zhang, Fan; He, Shengfu; Huang, Fu; Peng, Zhiyuan (Asian Journal of Chemistry, 2014)
Reduced graphene oxide was prepared by reducing graphene oxide with ethylenediamine. The adsorption behavior of the reduced graphene oxide for Pb(II), Cd(II), Cu(II) and Mn(II) was studied and the effects of media pH, adsorption time and initial metal ion concentration on adsorption capacity of the adsorbent were investigated. The adsorption capacities of reduced graphene oxide were found to be 413.22, 162.33, 55.34 and 42.46 mg/g for Pb(II), Cd(II), Cu(II) and Mn(II), respectively and the adsorption reaches equilibrium within 60 min. Experimental data were exploited for kinetic evaluations related to the adsorption processes. Adsorption kinetic data can be satisfactorily described by the pseudo-second-order equation and the Langmuir adsorption model agrees well with the experimental data. The adsorption capacity of reduced graphene oxide for Pb(II) decreased not more than 20 % for the three cycles, indicating the feasibility of reduced graphene oxide adsorbent in metal recovery and removal.